(untitled) (Research, Society and Development, 2022)
Individuals with a deficiency in the immune system are more likely to develop oral lesions, which can be seen in 70-90% of patients with the Human Immunodeficiency Virus (HIV). Therefore, the objective of this study is to identify in the literature the oral manifestations prevalent in HIV-positive individuals, as well as the behavior of the dentist. This is a narrative literature review, of an explanatory nature, carried out by means of a survey in the electronic databases: PubMed, LILACS, SciELO, BVS, Scholar Google, in the period between 2010 and 2022. For the search, the Descriptors in Health Sciences (DeCS): "candidiasis", "periodontal diseases", "herpes simplex", "oral hairy leukoplakia", "kaposi’s sarcoma", "non-hodgkin’s lymphoma", with the association of the Boolean operators AND and OR for the terms “HIV” and “dentistry”. 42 references were selected for the study. According to the literature studied, it became evident that oral manifestations are present in patients with HIV, presenting lesions with clinical and intensity variations, which can develop according to the susceptibility of the immune system and the stage of natural evolution of the disease. These include candidiasis, herpes simplex, periodontal diseases, oral hairy leukoplakia, Kaposi’s sarcoma and non-Hodgkin’s lymphoma. Oral manifestations are usually the first evidence of the presence of HIV. In this way, the importance of the role of the dentist is evidenced, as this professional can act in the early diagnosis, favoring an appropriate therapy and reduction of morbidity.